2003
DOI: 10.1117/12.506135
|View full text |Cite
|
Sign up to set email alerts
|

<title>Road-constrained target tracking and identification a particle filter</title>

Abstract: 532 Downloaded From: http://proceedings.spiedigitallibrary.org/ on 06/02/2015 Terms of Use: http://spiedl.org/terms Proc. of SPIE Vol. 5204 533 Downloaded From: http://proceedings.spiedigitallibrary.org/ on 06/02/2015 Terms of Use: http://spiedl.org/terms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 12 publications
0
27
0
Order By: Relevance
“…Some of these approaches can be used with Kalman filtering, such as reparameterizing the problem [54]. Other approaches are specific to particle filtering, such as modifYing the particles' likelihood functions based on their level of constraint satisfaction [55,56] or generating process noise which ensures that the propagated particles satisty the constraints [57].…”
Section: Particle Filtersmentioning
confidence: 99%
“…Some of these approaches can be used with Kalman filtering, such as reparameterizing the problem [54]. Other approaches are specific to particle filtering, such as modifYing the particles' likelihood functions based on their level of constraint satisfaction [55,56] or generating process noise which ensures that the propagated particles satisty the constraints [57].…”
Section: Particle Filtersmentioning
confidence: 99%
“…In cases of multiple-hypothesis tracking of a single target, the belief updating is traditionally done with particle filters ( [4], [5], [6]). An exception is [19], which explores both the Gaussian sum approximation and particle filter approaches.…”
Section: Related Workmentioning
confidence: 99%
“…As the agent does not have perfect information of the targets' poses and their subsequent actions, it has to reason about its belief of their poses when planning to keep them well-localized. Traditionally, although targetsearch algorithms [1], [2], [3] necessarily involve planning under uncertainty, target-following algorithms [4], [5], [6] typically focus on performing accurate belief updating and data association, rather than tackling the decision-making challenges faced by the agent. Especially when multiple targets have to be tracked by a single agent, the agent has the additional challenge of reasoning about which target to concentrate on at every timestep.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that this tracking can be improved further by exploiting any additional known structure from the problem (e.g. road network) [7], [8]. However, it is not always possible to obtained such a structured set of constraints which dictate object movement (e.g.…”
Section: Introductionmentioning
confidence: 99%